THE LEFT VENTRICULAR EJECTION FRACTION AND THE LEFT ATRIAL ANTEROPOSTERIOR DIAMETER AS PREDICTORS OF ACUTE ISCHEMIC STROKE OUTCOME - Munjiza, Dejan; Georgievski-Brkić, Biljana; Vitošević, Filip; Vukićević, Marjana (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Acute stroke represents a significant health burden. Since the variables obtained by transthoracic echocardiography are proven predictors of the outcome of cardiac diseases, we tried to determine their importance in predicting the outcome of this group of patients. The aim of the work is to prove the hypothesis that the enlargement of the left atrium, expressed by the increase in the anteroposterior diameter and the decrease in the systolic function of the left ventricle, as observed by the value of the ejection fraction, predict a bad outcome in these patients. Material and methods: The methodology is based on the data analysis of 106 patients with acute ischemic stroke, including data on the modified Rankin score at discharge, which indicates the disease’s functional outcome. Results: A correlation was shown between the functional outcome of the disease in relation to the ejection fraction of the left ventricle. As the ejection fraction of the left ventricle decreases, the possibility of a worse disease outcome increases. The size of the left atrium was also tested as a predictor of a worse outcome in terms of a larger left atrium associated with a worse outcome of the disease, and the hypothesis proved to be correct here as well, given that there is a correlation between the size of its diameter and the outcome of the disease. Conclusion: The monitored parameters, the left ventricular ejection fraction and the left atrium size, show predictive value for the disease’s functional outcome.